Determination of Depression, Anxiety, Stress and Coronavirus Anxiety Levels of Parents Waiting for PCR Test Results - Mevhibe Çoban; Esra Güney (Genel Tıp Dergisi, 2022)
Aim: This study was aimed to determine the depression, anxiety, stress and coronavirus anxiety levels of parents waiting for PCR test results. Methods: The cross-sectional study was conducted between April-October 2021. The sample of the study consisted of 372 parents determined by power analysis. Data were collected from parents awaiting their children's PCR test results in the pediatric COVID service of the Training and Research Hospital in a province in the Eastern Anatolia Region. Data were collected using a personal information form, Depression Anxiety Stress Scale and Coronavirus Anxiety Scale. Results: According to the study, it was determined that parents with had ≥3 children, who were ≥36 years old, married for ≥11 years, educated at high school and below had higher levels of depression, anxiety, stress and coronavirus anxiety. It was determined that the anxiety levels of the women were higher than the men, and the difference between the parents' total Coronavirus Anxiety Scale score averages was statistically significant(p0.05). Conclusion: It was determined that PCR testing from their children due to the suspicion of COVID-19 caused depression, anxiety, stress and anxiety in parents, and the anxiety level of women was higher than men. Accordingly, parents should be given the opportunity to determine their anxiety and stress and take initiatives for it, and appropriate counseling services should be provided to reduce anxiety and stress during the pandemic process.